Enhancing the Decision-Making Virtuous Cycle of Ethical Banking Practices Using the Choquet Integral - Ferreira, J.; Jalali, M.; Ferreira, F. (2017 GIKA International Conference, 2017)
Although increasingly demanded of the sector, aligning ethical management and ethical principles in the banking activity is a challenging endeavor, due to the existence of conflicts of interest. Grounded on a previously developed cognitive map on ethical banking practices (Ferreira et al., 2016a), the current study uses the Choquet integral – a non-additive multiple criteria decision analysis (MCDA) operator – to help prioritize and weight the determinants of ethical banking. The results of the performance evaluation conducted on the ethical practices of the four largest banks operating in Portugal, confirm that the use of the Choquet integral allows for the improvement of the evaluation stage of the decision-making virtuous cycle of ethical banking. Strengths and limitations of the framework are also discussed.